2019
DOI: 10.1162/rest_a_00774
|View full text |Cite
|
Sign up to set email alerts
|

Defaults and Donations: Evidence from a Field Experiment

Abstract: We study the effects of defaults on charitable giving in a large-scale field experiment on an online fundraising platform. We exogenously vary default options along two choice dimensions: the charitable donation decision and the “co-donation” decision regarding how much to contribute to supporting the platform. We document a strong effect of defaults on individual behavior but nevertheless find that aggregate donation levels are unaffected by defaults. In contrast, co-donations increase in the default amount. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 40 publications
4
23
0
Order By: Relevance
“…Also, defaults not only affect happiness but also have a direct effect on decisions. Consistent with a large literature on nudging, we found that more people chose personal spending when this was the default than when this was one of two options (Altmann et al, 2019;Johnson & Goldstein, 2003). However, this effect was rather small since most participants still chose to opt out from the personal spending default.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Also, defaults not only affect happiness but also have a direct effect on decisions. Consistent with a large literature on nudging, we found that more people chose personal spending when this was the default than when this was one of two options (Altmann et al, 2019;Johnson & Goldstein, 2003). However, this effect was rather small since most participants still chose to opt out from the personal spending default.…”
Section: Discussionsupporting
confidence: 87%
“…A default is the preselected option that will be chosen when an active decision is not made (Dinner et al, 2011;Johnson & Goldstein, 2003). Defaults have been shown to be effective in several domains, such as changing people's decision about whether to donate organs or not (Johnson & Goldstein, 2003) and how much money people choose to donate to charity (Altmann et al, 2019;Zarghamee et al, 2017). Three reasons to why defaults work have been put forth; 1) defaults are perceived as the choice that policy makers recommend (i.e., endorsement), 2) sticking with the default does not require any effort (i.e., inertia), and 3) defaults work like points of reference that other options are compared to, so changing from the defaults requires some trade-off (i.e., status quo; Dhingra et al, 2012;Johnson & Goldstein, 2003).…”
Section: Choice and Happinessmentioning
confidence: 99%
“…It becomes increasingly possible to dynamically adapt default values in online environments based on, for example, the individual characteristics of decision makers. Altmann et al (2019) suggest that, because of their crowding out effect, defaults should be set above intrinsic motivation. Their structural model suggests that setting the default to twice the level of intrinsic motivation could result in up to 6.2% higher donation revenues relative to no default.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies find positive effects of higher suggestions on revenue (Adena, Huck, and Rasul 2014), others find no effects (Altmann et al 2018) or even detrimental effects (Adena and Huck 2019a;Reiley and Samek 2018). Most of the studies confirm, however, that defaults and suggestions bring more individuals to donate exactly the suggested amount but suggestions that are set too high lead to a reduction in the response rate (for a review of the early literature on suggestions, see Bekkers and Wiepking 2010).…”
Section: Defaults Suggestions and Donation Gridsmentioning
confidence: 99%